Meir (left) and Brandt (with plate) at Premier Ahti Karjalainen's reception for the SI Council Conference-participants - Hedenström, Kaius,
Meir (left) and Brandt (with plate) at Premier Ahti Karjalainen's reception for the SI Council Conference-participants.